Trichinella spiralis Infection Mitigates Collagen-Induced Arthritis via Programmed Death 1-Mediated Immunomodulation - Cheng, Yuli; Zhu, Xing; Wang, Xiaohuan; Zhuang, Qinghui; Huyan, Xu; Sun, Ximeng; Huang, Jingjing; Zhan, Bin; Zhu, Xinping (Frontiers in Immunology, 2018)
Helminth infection induces Th2-biasd immune responses and inhibitory/regulatory pathways that minimize excessive inflammation to facilitate the chronic infection of helminth in the host and in the meantime, prevent host hypersensitivity from autoimmune or atopic diseases. However, the detailed molecular mechanisms behind modulation on inflammatory diseases are yet to be clarified. PD-1 is one of the important inhibitory receptors involved in the balance of host immune responses during chronic infection. Here we used the murine model to examine the role of PD-1 in CD4+ T cells in the effects of Trichinella spiralis infection on collagen-induced arthritis (CIA). Mice infected with T. spiralis demonstrated higher expression of PD-1 in the spleen CD4+ T cells than those without infection. Mice infected with T. spiralis 2 weeks prior to being immunized with type Ⅱ collagen (CⅡ) displayed lower arthritis incidence and significantly attenuated pathology of CIA compared with those of uninfected mice. The therapeutic effect of T. spiralis infection on CIA was reversed by blocking PD-1 with anti-PD-1 antibody, associated with enhanced Th1/Th17 pro-inflammatory responses and reduced Th2 responses. The role of PD-1 in regulating CD4+ T cell differentiation and proliferation during T. spiralis infection was further examined in PD-1 knockout (PD-1-/-) C57BL/6 J mice. Interestingly, T. spiralis-induced alteration of attenuated Th1 and enhanced Th2/Treg differentiation in WT mice was effectively diminished in PD-1-/- mice characterized by recovered Th1 cytokine levels, reduced levels of Th2 and regulatory cytokines and CD4+CD25+Foxp3+ cells. Moreover, T. spiralis-induced CD4+ T cell proliferation suppression in WT mice was partially restored in PD-1-/- mice. This study introduces the first evidence that PD-1 plays a critical role in helminth infection-attenuated CIA in a mouse model by regulating the CD4+ T cell function, which may provide the new insights into the mechanisms of helminth-induced immunomodulation of host autoimmunity.